Propriedades físico-hídrico-mecânicas de um latossolo vermelho em plantio direto escarificado sobre o rendimento de grãos de milho - Klein, Claudia (2011)
The no-tillage has proves to be a conservationist system for excellence, being the compaction originated from the unplowed soil and pressure exerted by the machines and machinery on these areas the major obstacle of this system, especially for not considering the optimum moisture content. An alternative for these areas is sporadic soil chiseling that has proven to be increasingly efficient to eliminate or minimize the effect of this compaction, aimed improving the soil structure quality for crop development. The goal of this study was to evaluate the changes in the physical, hydraulic and mechanical properties of a Dystrophic Red Oxisol humic in Passo Fundo (RS), under no-tillage system for 12 years, as well as, the effect of chiseling in the soil properties and the oat development and corn yield. The following parameters were measured: bulk and particle density, relative density, porosity, least limit water range, soil water retention, variation of water storage in the row and interrow, saturated soil hydraulic conductivity and biometric parameters of black oat (fresh and dry mass, height) and corn (ear, grain and corncob mass, culm diameter) and corn plant density. Concluded that chiseling is an efficient practice to minimize soil compaction and decreases soil bulk density and relative density, increases total soil porosity especially macropores, reduces the resistance to penetration, increases the water available to the plants and can provide higher yields of dry mass in oat, thereby offering more plant residue mulches, and greater corn yield